The Political Influence of Voters’ Interests on SEC Enforcement - Heese, Jonas (Contemporary Accounting Research, 2019)
ABSTRACT I examine whether political influence as a response to voters’ interest in employment levels is reflected in the enforcement actions of the SEC. I find that large employers are less likely to experience SEC enforcement actions. Next, I examine whether variations in politicians’ sensitivity to employment levels result in variations in enforcement against large employers. I find that large employers are less likely to face enforcement actions during presidential elections if they are based in politically important states. Large employers also face fewer enforcement actions if they are based in high‐unemployment states during elections of senators who serve on SEC oversight committees. Large employers based in high‐unemployment districts enjoy lower enforcement if their members of Congress serve on SEC oversight committees. The findings suggest that voters’ interests are reflected in SEC enforcement.